Targeting Liver Biopsies For Optimal Biopsy Site In Diffused Liver Disease Using Real-Time Shear Wave Elastography: A Prospective, Single Center Study - Naushaba Malik; Shahbakht Aftab; Rida Noor; Noor Aftab; Rizwan; Rehan (Journal of Rawalpindi Medical College)
Objective: The study aimed to pinpoint the precise site for liver biopsy using ultrasound and elastography guidance and to assess and compare the diagnostic accuracy of shear wave elastography (SWE) and transient elastography (TE) through histopathological correlation.